Holistic Supervision of the Judges of the Indonesian Constitutional Court - Sadzali, Ahmad; Ghafur, Jamaludin; Rishan, Idul (KnE Social Sciences, 2023)
The issuance of the latest Constitutional Court Law, Law Number 7 of 2020 on the Third Amendment to Law Number 24 of 2003 on the Constitutional Court, does not bring significant changes in the mechanism for monitoring constitutional court justices and the enforcement of the Code of Ethics and Conduct of Constitutional Justices. This paper aimed to offer a more holistic means of supervising constitutional court judges. The idea is a triangle of supervision consisting of internal control of individual judges, internal control of the institution, and external supervision. Keywords: Supervision of Judges/Justices, Constitutional Court, Code of Ethics, Judges Integrity